Remediation of Polychlorinated Biphenyls (PCBs) in Contaminated Soils and Sediment: State of Knowledge and Perspectives - Jing, Ran; Fusi, Soliver; Kjellerup, Birthe V. (Frontiers in Environmental Science, 2018)
Polychlorinated biphenyls (PCBs) are one of the persistent organic pollutants (POPs) used worldwide between the 1930s and 1980s. Many PCBs can still be found in the environment such as in soils and sediments, even though their use has been heavily restricted. This review summarizes the most frequent remediation solutions including, phytoremediation, microbial degradation, dehalogenation by chemical reagent, and PCBs removal by activated carbon. New insights that emerged from recent studies of PCBs remediation including supercritical water oxidation, ultrasonic radiation, bimetallic systems, nanoscale zero-valent iron based reductive dehalogenation and biofilm covered activated carbon, electrokinetic remediation, and nZVI particles in combination with a second metal are overviewed. Some of these methods are still in the initial development stage thereby requiring further research attention. In addition, the advantages and disadvantages of each general treatment strategy and promising technology for PCBs remediation are discussed and compared. There is no well-developed single technology, although various possible technologies have been suggested. Therefore, the possibility of using combined technologies for PCB remediation is also here investigated. It is hoped that this present paper can provide a basic framework and a more profound prospect to select successful PCB remediation strategies or combined technologies.